2013
DOI: 10.1016/j.mod.2012.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Natural variation of the root morphological response to nitrate supply in Arabidopsis thaliana

Abstract: Nitrogen fertilization increases crop yield but excessive nitrate use can be a major environmental problem due to soil leaching or greenhouse gas emission. Root traits have been seldom considered as selection criteria to improve Nitrogen Use Efficiency of crops, due to the difficulty of measuring root traits under field conditions. Nonetheless, learning about mechanisms of lateral root (LR) growth stimulation or repression by nitrate availability could help to redesign root system architecture (RSA), a strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 49 publications
5
39
0
Order By: Relevance
“…The most important example of the plasticity that plants express to fit with nutrient withdrawal in soil is, in fact, represented by the capability of rearranging root architecture to maximize their capture (Lόpez-Bucio et al , 2003; Hermans et al , 2006; Zhang et al , 2007; Zolla et al , 2010; Giehl et al , 2012; De Pessemier et al , 2013). Nitrate affects root development by finely regulating the growth of lateral roots depending on its external concentration and localization, as aforementioned (Péret et al , 2009; Mounier et al , 2013; Yu et al , 2013) and as also showed by the current findings obtained with the WinRhizo software (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The most important example of the plasticity that plants express to fit with nutrient withdrawal in soil is, in fact, represented by the capability of rearranging root architecture to maximize their capture (Lόpez-Bucio et al , 2003; Hermans et al , 2006; Zhang et al , 2007; Zolla et al , 2010; Giehl et al , 2012; De Pessemier et al , 2013). Nitrate affects root development by finely regulating the growth of lateral roots depending on its external concentration and localization, as aforementioned (Péret et al , 2009; Mounier et al , 2013; Yu et al , 2013) and as also showed by the current findings obtained with the WinRhizo software (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The biochemical mechanisms involved in NO 3 uptake, assimilation and remobilization have been widely studied in order to identify the features that determine the nitrogen use efficiency (NUE) of a plant [2][3][4][5][6]. The effect of low N availability on plant biomass, NO 3 uptake, ion contents and root architecture has been widely investigated [7][8][9][10]. There is evidence that plants modify their root architecture, changing the lateral to primary roots ratio and decreasing the shoot-to-root ratio at the same time, to forage the soil for nutrients.…”
Section: Introductionmentioning
confidence: 99%
“…Plant responsiveness to N availability depends on both genotype and the interaction of genotype with N supply level [19]. Root architecture plasticity traits have been investigated in Arabidopsis in relation to N availability by De Pessemier et al [7]. This study, conducted on a core-collection of 24 accessions, together with the one conducted by Sulpice et al [20] on 97 Arabidopsis accessions for biomass traits in response to carbon (C) and N nutrition, confirms that a large genetic variation exists in response to nutrient availability within the same species.…”
Section: Introductionmentioning
confidence: 99%
“…According to Cao et al (2013) strict calcium deficiency resulted in reduced number of lateral roots in P. trifoliate as well. Furthermore, studies showed that under low P and N concentrations in media density or number of lateral roots in Arabidopsis increased (De Pessemier et al, 2013;Gruber et al, 2013;Niu et al, 2013). However, there are some reports showing the opposite tendencies.…”
Section: Resultsmentioning
confidence: 99%